Nominativus ja instructivus absolutus eräissä vanhan suomen ja varhaisnykysuomen aineistoissa - Forsman Svensson, Pirkko (Virittäjä, 2001)
Absolute nominative and absolute instructive in selected texts from old literary Finnish and early modern Finnish (englanti) 3/2001 (105) Pirkko Forsman Svensson ABSOLUTE NOMINATIVE AND ABSOLUTE INSTRUCTIVE IN SELECTED TEXTS FROM OLD LITERARY FINNISH AND EARLY MODERN FINNISH The absolute nominative construction (e.g. Hn hyppsi veteen p edell He jumped into the water head first) is an ancient feature of Finno-Ugrian languages, although similar free constructions can be found in other languages too. The absolute partitive construction (e.g. Hn tervehti tulijaa ihmetyst nessn He greeted the arrival, amazement in his voice) is believed to have been derived by analogy with the nominative construction. Both constructions are rare in modern Finnish. Still rarer is the absolute instructive (e.g. itkussa silmin with a tear in the eye, irvess suin with a grimace), the meaning of which can be paralleled with the other constructions mentioned. The absolute instructive is found almost exclusively in the Savo and Ostrobothnian dialects and is used, for example, to embellish journalistic texts. The article examines the use of the absolute nominative and absolute instructive in written Finnish from the eighteenth and early nineteenth centuries. The material includes eighteenth century religious texts written by fifteen different writers, about the same number of secular texts and the dictionary of Christfrid Ganander (1787). In addition, the writer used computerised corpora from the Research Institute for the Languages of Finland. The writer draws the following conclusions about the use of the absolute nominative. The number of occurrences increases from the seventeenth to the nineteenth century, although the frequency of use remains comparatively low as in modern Finnish, too. In texts from the latter half of the seventeenth century there were only a handful of occurrences, but in the material from the eighteenth century there were over 20. Gananders dictionary also featured about 20 occurrences. The material from the first half of the nineteenth century contained over 60 examples. In two of the rare occurrences in the seventeenth century texts, the local case expression in the construction is kdes, ksisns in the hand, in his hands, and in Gananders dictionary kde(s)s is likewise more common than other expressions. In the eighteenth century sources, kdes and its variants are clearly the most common, and more than half of the nineteenth century examples are kdess constructions. The expression jokin (esine) kdess (object) in the hand thus remained the dominant type of expression in absolute nominative constructions from old literary Finnish to early modern Finnish. About a dozen examples of the absolute instructive were found in the seventeenth century texts, but only a handful in those from the eighteenth century. By contrast, about 30 examples were found in the Gananders dictionary. More than ten examples from the early modern Finnish period are listed by Leskinen (1990), to which the writer adds about the same number found in the computer corpora. In the seventeenth century constructions the silmin instructive was in a slight majority. The most common instructives in the eighteenth century examples are ksin, silmin, suin and pin. The spectrum of examples is fairly wide, more common among them being hiuksin, huulin, kauloin, kidoin, korvin, reisin again names of body parts. The most common body part instructives in the nineteenth century material are pin (due to repeated occurrences in the Kalevala), silmin, suin and ksin. There were few examples, however, in relation to the amount of material. The use of the absolute instructive appears to have been more frequent in the seventeenth and eighteenth centuries than it is today: the examples in Gananders dictionary, at least, indicate that the construction was natural in everyday language, whereas in literature from the same period there are few examples. This shortage of examples also applies to the nineteenth century material, although certain verses from the Kalevala that contain instructive constructions are repeated, especially in Lnnrots works. Certain instructive constructions were certainly cultivated in early modern Finnish specifically as the result of the language in the Kalevala. Use of the absolute instructive is more limited than thet of the corresponding nominative construction. The absolute nominative can be used to express really quite complex relations, for which the more popular absolute instructive is not applicable. The dearth of free-standing instructives in contemporary written Finnish cannot be explained exclusively by the constructions popular label but also by the limitations of its use.